LEONAS PANAVAS (1942–2011): PERSONALITY, BOOK CULTURE AND BOOKBINDING - Kaunas, Domas (Knygotyra, 2017)
Leonas Panavas (1942‒2011) was a professional milling-machine operator at Vilnius metal-working plants who became a bibliophile and book binder due to his cultural aspirations. He was motivated by his complicated family and personal experiences as well as by his natural abilities. His book culture was developing in several directions. It was dominated by his collection of a personal library of scholarly bias, his strong inclination for reading, and bibliophily. Even though L. Panavas lacked higher education, his personal book culture surpassed not only that of an ordinary metal worker but also exceeded the competences achieved by some professionals in the humanities. The main motivation for his creative activities was bookbinding. It made up for the gaps in his specialized secondary education acquired in his younger days. With the aim of self-development, L. Panavas turned bookbinding into a way of life. To keep it going, he constantly solidified the material foundations of his craft, expanded the circle of his clientele and continuously perfected his professional skills and his style of binding. Striving for a qualitative progress, he made use of professional literature and expert consultations, visited exhibitions of original artefacts created by masters of binding and learned from them. The literature on bookbinding collected by him is valuable and diverse in content. It included the history of writing and book publishing, the methods and technology of binding, the graphics of type and ornamentation of covers, binding materials, and the restoration of ancient bookbindings. He did his best to familiarize himself with the professional publications on the related crafts (leather industry, paper making) in other countries (Russia, the United Kingdom, France, the USA, Czech Republic) even though, due to the lack of knowledge of foreign languages, he could not always use them to the best advantage. However, the bookbinder’s reading range was not limited to professional literature only. His reading interests were truly universal and they were satisfied by a well selected personal library specializing in the humanities. Its characteristic feature is preservation of books and respect for them. In the present study, research into L. Panavas’s book culture and bookbindings is based on his personal collection of over 150 professional bookbindings preserved by his family as well as on his private library and some documents. However, one feels the absence of more diverse archival material. A major part of bookbindings created by L. Panavas during 25 years of binding activities is dispersed in the private collections of his numerous customers. Researching them is a task for the future. Still, the study has made it possible to establish L. Panavas as an important participant of the Lithuanian book binding process during the period of the restoration of Lithuania’s statehood and its consolidation (1985‒2010) as well as a productive craftsman.